Optimizing the Development of Student Learning Outcomes in Indonesian Language Subjects through the Cooperative Integrated Reading Composition (CIRC) Learning Model for Class IV Students of SDN 237 Pinrang - Reski Reski; Rahmat Rahmat; Saleha Saleha (Edumaspul: Jurnal Pendidikan, 2024)
The optimization of students' learning outcomes in Indonesian language through the Cooperative Integrated Reading Composition (CIRC) model among fourth-grade students at SDN 237 Pinrang was investigated with the aim of enhancing their comprehension and writing skills. The study was conducted over three cycles using methods that encompassed planning, implementation, observation, and continuous reflection on the learning process. Results indicated significant improvement in student achievement: from 60% not yet proficient and 40% proficient in Cycle 1, to 50% proficient and 50% not yet proficient in Cycle 2, and reaching 90% proficiency with only 10% of students not yet proficient in Cycle 3. Data analysis involved ongoing formative evaluation to monitor individual and group progress. In conclusion, the CIRC model proved effective in enhancing Indonesian language learning outcomes among fourth-grade students at SDN 237 Pinrang, consistently supporting students' abilities in comprehending and expressing texts in writing.